2019
DOI: 10.17219/acem/105380
|View full text |Cite
|
Sign up to set email alerts
|

Silicon intake and plasma level and their relationships with systemic redox and inflammatory markers in rheumatoid arthritis patients

Abstract: H. Silicon intake and plasma level and their relationships with systemic redox and inflammatory markers in rheumatoid arthritis patients. AbstractBackground. The nutritional significance of silicon for the human body is highlighted by a continually growing body of evidence. In conditions of excessive reactive oxygen species and upregulated immune response, silicon has been observed to provide benefits, but its role in redox and inflammatory status has not yet been examined in rheumatoid arthritis (RA).Objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 40 publications
0
16
0
1
Order By: Relevance
“…A study evaluating the relationship between plasma silicon levels, redox status (total antioxidant status) and inflammatory markers (CRP, IL-6) in RA, reported that patients affected by RA presented elevated plasma silicon levels compared to controls. No correlation between plasma silicon and dietary silicon level was observed, although in RA patients a negative correlation between silicon intake and IL-6 and total oxidant status was found [175]. In a recent randomized, double-blind, placebo-controlled clinical trial, active RA patients received 1500 mg ginger powder (or placebo) daily for 12 weeks.…”
Section: Antioxidantmentioning
confidence: 99%
“…A study evaluating the relationship between plasma silicon levels, redox status (total antioxidant status) and inflammatory markers (CRP, IL-6) in RA, reported that patients affected by RA presented elevated plasma silicon levels compared to controls. No correlation between plasma silicon and dietary silicon level was observed, although in RA patients a negative correlation between silicon intake and IL-6 and total oxidant status was found [175]. In a recent randomized, double-blind, placebo-controlled clinical trial, active RA patients received 1500 mg ginger powder (or placebo) daily for 12 weeks.…”
Section: Antioxidantmentioning
confidence: 99%
“…This association was not observed for hot beverages (coffee and tea), which may be related to coffee and tea polyphenols affecting the availability of minerals [25]. However, in our recent study we noticed a positive association between plasma silicon and tea and coffee consumption in rheumatoid arthritis patients [8]. As the body silicon status in rheumatoid arthritis seems to be affected, other factors related to the disease may interfere with the associations found.…”
Section: Discussionmentioning
confidence: 84%
“…The direct measurement of silicon in plasma was performed by GF-AAS (PinAAcle 900, Perkin Elmer, USA) using the method of standard addition calibration described elsewhere [8]. The operating conditions and instrumental parameters for silicon measurement are summarized in Supplementary Table S1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations